Case report: Deep molecular remissions post two separate CD19-targeted chimeric antigen receptor T-cell therapies do not prevent disease from relapsing in Philadelphia chromosome-positive acute lymphoblastic leukemia - Tang, Yu; Fei, Xiaoming; Yu, Xianqiu; Cao, Jiang; Wang, Lixia; Lei, Fang (Frontiers in Oncology, 2023)
Philadelphia chromosome-positive acute lymphoblastic leukemia (Ph+ ALL) is an aggressive B-cell malignancy. The management of a relapsed Ph+ ALL patient is challenging. Currently, either allogeneic stem cell transplant (allo-SCT) or CD19-targeted chimeric antigen receptor T-cell (CAR T-cell) is usually employed as a salvage modality for a relapsed patient. However, there is few reports concerning cases which had both allo-SCT and multiple CAR T-cell therapies, and the optimal management of such patient is unclear. Here we reported a relapsed Ph+ ALL male who was first salvaged with an autologous CAR T-cell therapy followed by allo-SCT.Unfortunately, he had a second relapse even with complete molecular remission (CMR) response after 1 st CAR T and allo-SCT. This patient was then successfully salvaged by a second CAR T-cell product which is donor-derived. However, even with a CMR response once again following the second CAR T-cell therapy and prophylactic donor lymphocyte infusion, he experienced a molecular relapse and ponatinib was employed as the subsequent salvage treatment. He achieved a CMR response following ponatinib and was still in remission at the last follow-up. No ABL kinase mutation was detected during the whole course of disease. This case indicated that a repeated CD19-targeted CAR T-cell treatment is feasible and may be effective in a relapsed Ph+ ALL patient which had previous CAR T-cell and allo-SCT, even both CAR T-cell have the same construction. However, even with a deep response after each CAR T-cell therapy and allo-SCT, there is still a very small amount of undetectable leukemic cells. The optimal management of a Ph+ ALL patient had a deep response after a second CAR T-cell therapy deserves further exploration.